Modulation of titin and contraction-regulating proteins in a rat model of heart failure with preserved ejection fraction: Limb vs. Diaphragmatic Muscle - Vahle, Beatrice; Heilmann, Leonard; Schauer, Antje; Augstein, Antje; Jarabo, Maria-Elisa Prieto; Barthel, Peggy; Mangner, Norman; Labeit, Siegfried; Bowen, T. Scott; Linke, Axel; Adams, Volker (International journal of molecular sciences, 2024)
Heart failure with preserved ejection fraction (HFpEF) is characterized by biomechanically dysfunctional cardiomyocytes. Underlying cellular changes include perturbed myocardial titin expression and titin hypophosphorylation leading to titin filament stiffening. Beside these well-studied alterations at the cardiomyocyte level, exercise intolerance is another hallmark of HFpEF caused by molecular alterations in skeletal muscle (SKM). Currently, there is a lack of data regarding titin modulation in the SKM of HFpEF. Therefore, the aim of the present study was to analyze molecular alterations in limb SKM (tibialis anterior (TA)) and in the diaphragm (Dia), as a more central SKM, with a focus on titin, titin phosphorylation, and contraction-regulating proteins. This study was performed with muscle tissue, obtained from 32-week old female ZSF-1 rats, an established a HFpEF rat model. Our results showed a hyperphosphorylation of titin in limb SKM, based on enhanced phosphorylation at the PEVK region, which is known to lead to titin filament stiffening. This hyperphosphorylation could be reversed by high-intensity interval training (HIIT). Additionally, a negative correlation occurring between the phosphorylation state of titin and the muscle force in the limb SKM was evident. For the Dia, no alterations in the phosphorylation state of titin could be detected. Supported by data of previous studies, this suggests an exercise effect of the Dia in HFpEF. Regarding the expression of contraction regulating proteins, significant differences between Dia and limb SKM could be detected, supporting muscle atrophy and dysfunction in limb SKM, but not in the Dia. Altogether, these data suggest a correlation between titin stiffening and the appearance of exercise intolerance in HFpEF, as well as a differential regulation between different SKM groups.
Gesehen am 14.01.2025